Stochastic models for system failures - reliability and warranty analysis (2012)
Reliability is the probability that a component or system will perform as a particular function under conditions specified for a given period of time. From design, there is a need to deliver equipment or systems with the features desired by the customer and that are reliable, easily maintained, safe and economical during their lifetime. This thesis studies systems reliability through stochastic modeling and analysis. The focus is on the availability of unreliable systems as one the main performance measures. In particular, the work mission availability for a two-unit parallel system with preventive maintenance is also studied. Reliability of the system won't be completed without its warranty analysis. Warranties of products have become a critical segment of industrial environment. ?A warranty is the expression of the willingness of business to stand behind its products and services?. As such it is a badge of business integrity. In broad terms, a warranty is viewed both as an insurance policy and a repair contract. As an insurance policy, if the product becomes defective within a certain period, the manufacturer compensates the customer by repair or replacement